Employee Engagement Among Business Process Outsourcing Industries in a Freeport Zone Amidst the Pandemic - Hans Christian U Mondejar; John Mark R Asio (Journal of Social Entrepreneurship Theory and Practice, 2023)
Employee engagement emerged as one of the most important topics for HR managers and practitioners in the industry. This study aims to analyze and assess how various organizations engaged their workers throughout the coronavirus epidemic. The Philippine Business Process Outsourcing (BPO) companies have shifted remote work set-up to ensure productivity. The researchers focused on 100 purposively selected managers and team leaders of BPO companies in a particular freeport zone in the Philippines. The proponents utilized a descriptive-correlation research design with the help of a modified survey instrument. Statistical analyses used were mean and Pearson-r moment of correlation with the help of SPSS 20. Results show that the respondents gave the study a remark of "sometimes" on their employee engagement. As for the perceived factors affecting employee engagement, career development, leadership, and work-life balance generated a response of "strongly agree" among the respondents, and only rewards and recognition got an "agree" response. Furthermore, the study also found a low to moderate positive association between employee engagement and the perceived factors affecting employee engagement. As concluded, a relationship exists between employee engagement, career development, leadership, work-life balance, and rewards and recognition within the organization. The importance of sustaining employee engagement amid the Covid-19 Pandemic is vital to attain productivity, and outcomes such as increased profit, lower absenteeism, and good health of employees are essential to achieve a win-win situation between the company and its stakeholders.